The impact of mobile telecommunication service quality on tourists’ destination satisfaction in Sarawak - Sin, Kit Yeng; Hariz Afiq, Shamsu; Choon Ling, Sim (Journal Management System, 2022)
Although Sarawak is a state in Malaysia with numerous interesting tourist destinations, tourist satisfaction is crucial for Sarawak's tourist destinations and is generally aected by the service quality. Generally, mobile telecommunication is essential for individuals nowadays. Therefore, the study aims to identify the impact of mobile telecommunication service quality on tourists' destination satisfaction in Sarawak. The service quality model (SERVQUAL) was used to measure the service quality of mobile telecommunication. The Statistical Package for the Social Sciences (SPSS v.26) was also applied to access the research model enveloped. Besides, the study used a simple random sample technique and collected 200 questionnaires from respondents who were local and foreign tourists visiting Sarawak. The results showed that reliability, assurance, tangible, empathy, and responsiveness of mobile telecommunication service quality have signicantly inuenced tourists' destination satisfaction in Sarawak. The results also indicated that Sarawak tourism destinations should be improved to increase tourists' tendency to revisit.